(untitled) (Research, Society and Development, 2022)
The use of innovative systems aims to optimize and qualify the construction execution process. They are usually prefabricated, allowing cost savings, lightness, and strength. Thus, the search for composite materials has been gaining ground, but the lack of studies on behavior and performance can impact the quality of these systems, and consequently, the emergence of pathological manifestations. In this scenario, this study intent is to identify pathological manifestations in two children’s schools in the city of Canoas/RS, built with an innovative and conventional system. For this, the history of the building in study was taken into account and a diagnosis of the possible causes was presented through the study of the behavior of the systems, executed with WS panels or with common masonry. With the survey of the pathological manifestations found, the gravity, urgency and tendency matrix tool (GUT) was applied to determine the degree of prioritization for solving the manifestation. As a result, it was noticed that the most frequent damages in the building are the segregation of the panels, which presented itself with greater occurrence in the building. In addition, the degradation of the coating and moisture stains also appear in a large part of the building, totaling these three damages with 62.5% of the total identified manifestations.